Degradation of methomyl by the combination of Aminobacter sp. MDW‐2 and Afipia sp. MDW‐3. (27th February 2017) - Zhang, C.; Yang, Z.; Jin, W.; Wang, X.; Zhang, Y.; Zhu, S.; Yu, X.; Hu, G.; Hong, Q.
Abstract : Abstract: Methomyl ( S ‐methyl N ‐(methylcarbamoyloxy) thioacetimidate) is a kind of oxime carbamate insecticide. It is considered to be extremely toxic to nontarget organism. To date, no pure culture or consortium has been reported to have the ability to degrade methomyl completely. In this study, a methomyl‐degrading enrichment E1 was obtained by using the sludge from the wastewater‐treating system of a pesticide manufacturer as the original inoculant. Two bacterial strains named MDW‐2 and MDW‐3 were isolated from this enrichment, and they were preliminarily identified as Aminobacter sp. and Afipia sp. respectively. Strains MDW‐2 and MDW‐3 could coexist and degrade 50 mg l −1 methomyl completely within 3 days by the cooperative metabolism. Methomyl was first converted to methomyl oxime and methylcarbamic acid by strain MDW‐2, and the latter could be used as the carbon source for the growth of strain MDW‐2. But methomyl oxime could not be sequentially degraded by strain MDW‐2. However, it could be degraded and used as the carbon source by strain MDW‐3. Significance and Impact of the Study: This study presents a bacterial combination of Aminobacter sp. MDW‐2 and Afipia sp. MDW‐3, which could degrade methomyl completely by biochemical cooperation. This study also proposes the biodegradation pathway of methomyl for the first time and highlights the application potential of a bacterial combination in the remediation of methomyl‐contaminated environments. Abstract : Significance and Impact of the Study: This study presents a bacterial combination of Aminobacter sp. MDW‐2 and Afipia sp. MDW‐3, which could degrade methomyl completely by biochemical cooperation. This study also proposes the biodegradation pathway of methomyl for the first time and highlights the application potential of a bacterial combination in the remediation of methomyl‐contaminated environments.